Lean Operations Implementation at An Indonesian Shoe Producer - Antonio, Bonny Tofani; Kusumastuti, Ratih Dyah (The South East Asian Journal of Management, 2019)
Research Aims: We analyse the impact of lean operations implementation on the performance of an Indonesian shoe producer, identify key success factors of the implementation and propose further improvements to increase company performance Design/Methodology/Approach: A mix of quantitative and qualitative methods is employed. Comparisons of operational and financial performance before and after implementation are conducted to analyse the program's impact. In-depth interviews with six representatives from the shoe producer and its vendor are conducted to rank the key success factors and gain insights into their lean operations implementation. Research Findings: The shoe producer experienced a significant increase in performance after implementing lean operations, and the five most important success factors of the implementation were management commitment and involvement, teamwork, communication, cultural-change management and sustainability of improvement activities. The current performance can still be improved by utilising information technology, implementing a Kanban system, providing direct delivery of raw materials and reducing lead times. Theoretical Contribution/Originality: The paper provides new insights into the challenges faced by the Indonesian shoe producer, especially in its operations and highlights five critical success factors of lean operations implementation. Managerial Implications in the Southeast Asian Context: Results of the present study can be used by other companies in a similar industry in the region to improve their operations and financial performance. Research Limitations and Implications: The impact of implementing lean operations with the proposed improvements to the company's costs and revenues has not been studied in detail.